2021
DOI: 10.1159/000518059
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of NICE Guideline CG149 and the Sepsis Risk Calculator for the Management of Early-Onset Sepsis on the Postnatal Ward

Abstract: <b><i>Introduction:</i></b> The NICE guideline CG149 has increased the number of well infants receiving antibiotics for suspected early-onset sepsis (EOS). The Kaiser Permanente sepsis risk calculator (SRC) has safely and dramatically reduced investigations and antibiotics for suspected EOS in the USA. This study evaluates the current management of suspected EOS against the NICE guideline CG149 and the SRC. <b><i>Methods:</i></b> This study is a prospective, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Seven confirmed cases of EONS were reported in this period, all of which received a recommendation to start or consider antibiotics according to EOSCalc. However, one of these cases did not receive this recommendation according to the Colombian CPG, which might suggest that EOSCalc displays greater sensitivity for EONS 1,12,28,29 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Seven confirmed cases of EONS were reported in this period, all of which received a recommendation to start or consider antibiotics according to EOSCalc. However, one of these cases did not receive this recommendation according to the Colombian CPG, which might suggest that EOSCalc displays greater sensitivity for EONS 1,12,28,29 .…”
Section: Discussionmentioning
confidence: 97%
“…The results presented here should not be interpreted as a suggestion to disregard local guidelines or expert recommendations, which can help inform the decision-making process of physicians in high-risk clinical scenarios. Risk assessment calculators should simply be an additional tool to be used in clinical practice (1). A potential reduction in unnecessary antibiotic use could mitigate the effects of alterations in the intestinal microbiota, such as the development of chronic illnesses [8][9][10][11][12][13][14][15][16][17][18][20][21][22]34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of different risks and clinical statuses correspond to different workup and treatment protocols [ 14 , 15 , 16 ]. Recent publications demonstrated that the EOS calculator, compared to conventional management strategies, shows lower relative risks for empirical antibiotic therapy without affecting safety [ 16 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%